Sono e síndrome da fragilidade em idosos residentes em instituições de longa permanência - Nóbrega, Patrícia Vidal de Negreiros (2011)
Introduction: The aging process causes quantitative and qualitative changes in sleeping. Such changes affects more than half of the adults above 65 years old, that live in the community and 70% of the institutionalized, a great negative impact in their quality of life. One of the pathological displays of aging, that share some characteristics with sleeping disorders and predict similar results, is the Frailty Syndrome, that characterize the most weakened and vulnerable elderly. The way sleeping disorders play a role in the frailty pathogeneses remains uncertain. Objective: Evaluate the relation between the sleeping and the frailty syndrome on institutionalized elderly. Methodology: A transversal study was performed with 69 elderly in institutions in the city of João Pessoa PB. Were used the Pittsburgh Sleeping Quality Index and actigraphy to subjective and objective variables, respectively, and questionnaires and specific tests to frailty phenotype variant (Fried Frailty Criteria). In the statistic analysis were used the Pearson correlation test, Chi Square and One-way ANOVA test, with Tukey-Krammer posttest. Subsequently, a Simple Linear Regression model was built. On every statistical analysis were considered a confidence interval of 95% and a p < 0,05. Results: The sample was characterized by the prevalence of the frail (49,3%), women (62,3%), single (50,7%) and 77,52 (±7,82).The frail elderly obtained the worst sleeping quality 10,37 (±4,31) (f = 4,15, p = 0,02), when compared with the non-frail. The sleep latency influenced more the frailty (R2 = 0,13, β standard = 1,76, β = 0,41, p = 0,001). Weren t found differences between the standard resting-activity variable and the frailty phenotype categories. Conclusion: Sleeping alterations, including bad sleeping quality, prolonged sleep latency, low sleep efficiency and day drowsiness, influenced the frailty in institutionalized elderly